Síntese e avaliação in vitro da atividade Leishmanicida de novos adutos de Morita-Baylis- Hillman (AMBH) híbridos com os constituintes Eugenol - Carvacrol e timol - Xavier, Francisco José Seixas (2018)
Molecular hybridization is an important strategy in Medical Chemistry for the preparation of bioactive molecules. It is based on the junction of structural and biological features between two classes of different bioactive molecules, to form a new molecule with greater biological potential. In this study, we present the synthesis of thirty-three new molecular hybrids derived from Morita-Baylis-Hillman Adducts (MBHA) and the renewable constituents eugenol, carvacrol and thymol. In addition, we present in vitro biological evaluations against Leishmania amazonensis promastigote cells. The hybrids were synthesized in two synthetic steps, starting from the optimization and synthesis of the acrylates from the constituents eugenol, carvacrol and thymol, using (Oxalyl chloride/DMF in CH2Cl2 and experimental route using DCC/DMAP in CH2Cl2 as the best synthetic methodology, 68-76% isolated). Then the reactions of MBH between each acrylate were made with the respective aldehydes: benzaldehyde; o, m, p nitrobenzaldehydes; α,β-naphthaldehydes; p-F, pCl, p-brome benzaldehydes; p-methoxybenzaldehyde and 2,5dimethoxybenzaldehyde where all compounds were obtained in moderate and good yields (53-92%). The experimental optimization used eugenol as a phenolic additive, and the results showed that the addition of 20 mol% of eugenol in the reaction involving acrylate derived from eugenol and ortho-nitro benzaldehyde increases the reaction yield by 10% when compared to the reaction without additive. Spectroscopic studies, including mass spectra, have confirmed the chemical structures of all synthesized compounds. The in vitro assays in promastigote forms of Leishmania amazonensis showed that all ortho, meta and p- nitro substituted hybrids were much more active when compared to the activities of eugenol, carvacrol and thymol itself, as well as the corresponding conventional MBHA, evidencing the success of the use of the molecular hybridization approach. It should be noted that the eugenol-derived hybrid containing the nitro group in the ortho position showed the best leishmanicidal activity (IC50 = 4.71 μM) and complete absence of toxicity in red blood cells (CH50> 400.0 μM; SIcv> 84.92 = CH50/IC50) being also less toxic than the reference drug Amphotericin B (SIcv = 22.34 μM).